Imperfect Strangers : Americans, Arabs, and U.S.-Middle East Relations in the 1970s - Yaqub, Salim (Book collections on Project MUSE., 2016)
In Imperfect Strangers, Salim Yaqub argues that the 1970s were a pivotal decade for U.S.-Arab relations, whether at the upper levels of diplomacy, in street-level interactions, or in the realm of the imagination. In those years, Americans and Arabs came to know each other as never before. With Western Europe's imperial legacy fading in the Middle East, American commerce and investment spread throughout the Arab world. The United States strengthened its strategic ties to some Arab states, even as it drew closer to Israel. Maneuvering Moscow to the sidelines, Washington placed itself at the center of Arab-Israeli diplomacy. Meanwhile, the rise of international terrorism, the Arab oil embargo and related increases in the price of oil, and expanding immigration from the Middle East forced Americans to pay closer attention to the Arab world. Yaqub combines insights from diplomatic, political, cultural, and immigration history to chronicle the activities of a wide array of American and Arab actors--political leaders, diplomats, warriors, activists, scholars, businesspeople, novelists, and others. He shows that growing interdependence raised hopes for a broad political accommodation between the two societies. Yet a series of disruptions in the second half of the decade thwarted such prospects. Arabs recoiled from a U.S.-brokered peace process that fortified Israel's occupation of Arab land. Americans grew increasingly resentful of Arab oil pressures, attitudes dovetailing with broader anti-Muslim sentiments aroused by the Iranian hostage crisis. At the same time, elements of the U.S. intelligentsia became more respectful of Arab perspectives as a newly assertive Arab American community emerged into political life. These patterns left a contradictory legacy of estrangement and accommodation that continued in later decades and remains with us today.